G4P3A0 Hamil 30 Minggu Belum Inpartu dengan Partus Prematurus Imminens dan Ketuban Pecah Dini - Putu A.L Amrita Kirana; Nurul Islamy; Ade Yonata (Medula, 2020)
Imminent preterm is the presence of a threat in pregnancy with emergence signs in 20 weeks-37 weeks. Preterm premature rupture of membrane is rupture of chorioamniotic membrane before the onset of childbirth and occurs in gestational age less than 37 weeks.. This study is a case report. A 34 years old woman with preterm pregnancy come with complained of the release of amniotic fluid that is odorless and can not be held from seven hours before entering hospital and accompanied by two days before entering hospital. It is accompanied by pain that intermitently radiating to the waist but still rare. From physical examination found moderate sick in general condition, compos mentis, BP 120/70mmHg, pulse 100 x/min, respiratory rate 20 x/min, temperature 36,6oC. General examination within normal limits. In obstetric examination found that fundus uteri is 3 finger under proccesus xiphoideus (26 cm), his (+) 2x in 10 minutes duration 10-12 seconds, fetal heart rate 144 x/min. In inspekulo examination found that portio is livid, OUE closed, amniotic fluid (+) not active, erosion/laseration/polip (-), lakmus (+) red to blue. Vaginal toucher not performed in this patient. The diagnosis are G4P3A0 in 30 weeks pregnancy, not inpartu yet, with imminent preterm and premature rupture of membrane. Patient planned conservative therapy such as observation of his, fetal heart rate, and vital signs mother, IVFD RL gtt x x/min, dexamethasone 2x10 mg, nifedipine 4x10 mg, cefadroxil 2x500mg.